Atrial natriuretic peptide and posterior pituitary neurohormone changes in patients with acute schizophrenia - Guzel D (Dove Medical Press, 2018)
Derya Guzel,1 Ahmet Bulent Yazici,2 Tugba Mutu Pek,2 Songul Doganay,1 Alime Burcin Saykan Simsek,2 Kadir Saglam,1 Caglar Turan,2 Esra Yazici2 1Department of Physiology, School of Medicine, Sakarya University, Sakarya, Turkey; 2Department of Psychiatry, School of Medicine, Sakarya University, Sakarya, Turkey Objectives: Interactions between neuropeptides and psychiatric disorders have been investigated for many years. The aim of this study was to evaluate oxytocin (OXT), arginine-vasopressin (AVP), and atrial natriuretic peptide (ANP) and assess their interactions with each other, as well as investigate these changes with the manifestations of schizophrenia. Participants and methods: Thirty-four individuals having acute schizophrenia and 24 healthy individuals as the control group were included in the study. Positive and Negative Syndrome Scales, Global Assessment of Functionality score, and Clinical Global Impression (CGI) scores were measured. Serum hormone levels were analyzed using enzyme-linked immunosorbent assay and were compared with the clinical findings. Results: OXT levels were significantly lower and AVP levels were significantly higher in patients having acute schizophrenia than the control group. OXT was negatively correlated with Positive and Negative Syndrome Scales positive score and CGI score, while it was positively correlated with Global Assessment of Functionality score. AVP was negatively correlated with CGI score. ANP levels of the patients having schizophrenia were lower than the control group; however, there was no significant correlation with clinical findings. Conclusion: The obtained data indicate that the AVP level was higher, but OXT and ANP levels were lower in the patients having acute schizophrenia. Specifically OXT is related with reduced disease severity and increased functionality. Keywords: schizophrenia, oxytocin, PANS, GAF, CGI, AVP